Students’ English Vocabulary through “Kate Kulp” Tiktok Videos - Nurul Aida; Abdul Muin; Tatu Siti Rohbiah (English Education Department, Postgraduate, Universitas Sultan Ageng Tirtayasa, Indonesia, 2023)
This study investigates the students’ English vocabulary through “Kate Kulp” TikTok videos at Eighth Grade of MTs Nur El Falah Kubang. This research was conducted based on the statement of the problem: (1) How is the students’ vocabulary mastery of eighth-grade MTs Nur El Falah Kubang? (2) How is the effect of “Kate Kulp” TikTok videos on students’ English vocabulary mastery? This study used a quasi-experimental method with two classes: class VIII B as the experimental class and class VIII A as the control class. After collecting the data, the researchers analyzed the data using the t-test. Based on the results, the average pre-test in the experimental class is 42 and the average post-test in the experimental class is 88.33. Meanwhile, the average pre-test in the control class is 44.33 and the average post-test value in the control class is 79. According to the result of the data, the value of tobservation (3,18) > ttable (1,67) in 5%, and tobservation (3,18) > ttable (2,39) in 1%. So, Ho is rejected and Ha is accepted, which means “Kate Kulp” TikTok videos are effective towards students’ English vocabulary mastery.